Anatomical classification: a proposal to categorize cleft lip and palate - Leiva, Noemí (2019)
The origin of cleft lip and palate classification dates back to the early twentieth century. Many of the systems proposed by different authors have not prospered, mainly because of their complexity in memorizing and recording. This scientific note summarizes the most popular cleft lip and palate classifications among health professionals and also proposes a new one, based on anatomical and morphological features of the patient´s cleft; the Anatomical Classification. This classification, designed and used by the Craniofacial Malformations Unit of the University of Chile, seeks to provide a solution to this problem, categorizing the clefts, in a simple and descriptive manner, according to the tissues involved (lip, palate, lip and palate), if its clinical manifestation is not that prevalent (atypical) or if they are associated with some syndrome (syndromic).